Pembinaan Pelaporan Keuangan Untuk UMKM Wilayah Jakarta Timur - Hafifah Nasution; Hera Khairunnisa; Etty Gurendrawati; Aji Ahmadi Sasmi (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2020)
MSMEs as a business entity need reports in decision making. This decision is at least useful for the owner of the MSME itself. Information that can be retrieved is by knowing the ending balance of the business activities profit or loss. This service activity aims to provide knowledge and skills of MSME actors in a basic financial accounting environment. In the long term, making MSME financial reports can also be useful for seeking funding from banks or investors. This service program consists of several implementation stages: (1) Planning stage: this stage is for mapping problems carried out by the proposing team; (2) Implementation stage: this stage is for realizing solutions to partner problems identified at the beginning of this proposal; (3) Evaluation stage: this stage is an evaluation of activities and making reports on the results of PKM activities. The results of the evaluation of this activity indicated that the participants' ability regarding financial reporting for MSMEs increased. This can be demonstrated by the results of the practice questions given after the presentation of the material by the speaker.